2019 International Conference on Document Analysis and Recognition (ICDAR) 2019
DOI: 10.1109/icdar.2019.00224
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Hybrid Approach for Textual Document Classification

Abstract: Text document classification is an important task for diverse natural language processing based applications. Traditional machine learning approaches mainly focused on reducing dimensionality of textual data to perform classification. This although improved the overall classification accuracy, the classifiers still faced sparsity problem due to lack of better data representation techniques. Deep learning based text document classification, on the other hand, benefitted greatly from the invention of word embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…However, in the face of massive and chaotic network news information, the problem that users face is no longer how to find news resources, but how to efficiently and accurately obtain information that can meet their own needs from the massive news resources [6]. erefore, in order to meet the diverse and personalized needs of online news users in the context of the big data era, effective information organization and management of online news have become an urgent problem to be solved [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the face of massive and chaotic network news information, the problem that users face is no longer how to find news resources, but how to efficiently and accurately obtain information that can meet their own needs from the massive news resources [6]. erefore, in order to meet the diverse and personalized needs of online news users in the context of the big data era, effective information organization and management of online news have become an urgent problem to be solved [7].…”
Section: Introductionmentioning
confidence: 99%
“…The results of their experiments revealed that the CPAMF results were better than those of the cosine measure and BM25 by a healthy margin. For research article categorization, some authors have proposed hybrid approaches [19], [27], [28], [29], [30]. In these approaches, feature extraction is performed utilizing DL techniques and classification based on ML and DL methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Comparison against the performance with SVM, Rocchio algorithm, Bayes, Naïve Bayes is mentioned in the paper, however, authors have not provided the table or graph results. Some authors proposed hybrid approaches for textual document classification [21] [22] [23]. In hybrid approaches, the algorithms focused on both feature extraction using deep learning and classification using machine and deep learning.…”
Section: Related Workmentioning
confidence: 99%